The development of tuna patties from skipjack (Katsuwonus pelamis) and the effects of freezing of their keeping quality. - Dematera, Ana Renee M. (College of Fisheries, University of the Philippines, 1979)
Various product formulations for tuna patties were prepared. The amounts of species and cornstarch were principally considered. The levels of spices included the following combinations: 15% onion, 25% pickle; 20% onion, 20% pickle; 25% onion, 15% pickle. Samples were evaluated subjectively and data were treated statistically by the Analysis of Variance. Results showed no significant differences among samples although the sample with an equal amount of onion and pickle obtained the highest acceptability scores and so was chosen for the subsequent tests. For the suitable percentage of cornstarch, samples with 5%, 10% and 15% were tested. Subjective evaluation showed significant differences among samples at 1% and 5% levels of probability with respect to texture, flavor and general acceptability. Statistics showed that the sample with 10% cornstarch as binder was most liked. The final sample with the 20% onion, 20% pickle and 10% corn starch was then analysed for proximate composition. In the second phase, the most acceptable product was stored in a home freezer at 14%F (-10c) for two, four and six weeks. Subjective and objective evaluations were carried out at each storage period. The sample at zero storage time was likewise evaluated. There was no considerable deterioration among samples at various storage time shown by sensory evaluation. Objective evaluation, on the other hand, showed similar assessment. Microbial examination resulted to insignificant bacterial load. Peroxide value as an index of oxidation increased as storage time progressed while moisture content decreased. Nevertheless, product was still acceptable up to the sixth week of cold storage.